2017
DOI: 10.1007/s13592-017-0494-6
|View full text |Cite
|
Sign up to set email alerts
|

Areas of endemism in the Atlantic Forest: quantitative biogeography insights from orchid bees (Apidae: Euglossini)

Abstract: Orchid bees are endemic to the Neotropics and were sampled more intensively in the Atlantic Forest in the last decade than in that of other Brazilian biomes. In this study, we aimed at identifying the main distributional patterns and areas of endemism of Euglossini orchid bee species in the Atlantic Forest using parsimony analysis of endemism and endemicity analysis. The results of these analyses were partly congruent and supported the idea that the distribution of orchid bees is structured into at least five … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
16
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 47 publications
1
16
1
Order By: Relevance
“…Based on orchid bee distributions, Garrafoni et al . [ 42 ] found at least five main AoE, which are congruent with those from Silva & Casteleti [ 24 ], varying only in size.…”
Section: Introductionsupporting
confidence: 83%
“…Based on orchid bee distributions, Garrafoni et al . [ 42 ] found at least five main AoE, which are congruent with those from Silva & Casteleti [ 24 ], varying only in size.…”
Section: Introductionsupporting
confidence: 83%
“…Contrary to what have been shown for Atlantic Forest in Brazil (Garraffoni et al, 2017;Nemésio and Santos-Junior, 2014), we did not find endemic species of BEC. Pearson and Dressler (1985) suggested that orchid bees apparently were not affected by historical isolation and speciation events occurred on forest refuges during the Pleistocene.…”
Section: Discussioncontrasting
confidence: 99%
“…Euglossa cordata and Eulaema nigrita were also the two-dominant species in the Santa Genebra forest in 2008 (Cordeiro et al, 2013) and in other Atlantic Forest fragments Gaglianone, 2008, 2012;Ramalho et al, 2009;Rocha-Filho and Garófalo, 2013;Oliveira et al, 2015). Both species are distributed throughout the Atlantic Forest (Garraffoni et al, 2017), and can be found in disturbed and fragmented areas as well as in open preserved areas (e.g., Viana and Kleinert, 2006;Ramalho et al, 2009;Aguiar and Gaglianone, 2012).…”
mentioning
confidence: 96%
“…They are well-known and widely distributed taxon in the Atlantic Forest with more than 60 species (included in four distinct genera) registered in this biome (Nemésio, 2009;Garraffoni et al, 2017). The Atlantic Rain Forest originally occupied about 15% of the Brazilian territory, but it was completely fragmented in forest remnants, and now covers 11-16% of its original area (Ribeiro et al, 2009;Joly et al, 2014).…”
mentioning
confidence: 99%
See 1 more Smart Citation